1998
DOI: 10.2105/ajph.88.10.1542
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of condom use among adolescents: the impact of mother-adolescent communication.

Abstract: Efforts to promote condom use by sexually active young people are an important component of the public health strategy to We hypothesized that early mother-adolescent condom discussions would promote condom use at first intercourse and that condom use at first intercourse would promote subsequent condom use. Methods Study PopulationThe sample was composed of 372 sexually active adolescents from the Family and Adolescent Risk Behavior Study, a crosssectional interview study conducted in New York, Alabama, and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
193
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(204 citation statements)
references
References 22 publications
8
193
2
1
Order By: Relevance
“…Instrumental parenting characteristics such as permissiveness and monitoring are also related to teens' sexual experience. Later sexual debut is associated with more parental monitoring, less parental permissiveness, and the presence of household routines and rules (Danziger, 1995;Li et al, 2000;Metzler et al, 1994;Miller et al, 1998Miller et al, , 1999Romer et al, 1994Romer et al, , 1999. Parental monitoring reduces opportunities for early sexual activity by limiting adolescents' exposure to sexual possibility situations (Paikoff, 1995).…”
Section: Parenting Stylesmentioning
confidence: 99%
“…Instrumental parenting characteristics such as permissiveness and monitoring are also related to teens' sexual experience. Later sexual debut is associated with more parental monitoring, less parental permissiveness, and the presence of household routines and rules (Danziger, 1995;Li et al, 2000;Metzler et al, 1994;Miller et al, 1998Miller et al, , 1999Romer et al, 1994Romer et al, , 1999. Parental monitoring reduces opportunities for early sexual activity by limiting adolescents' exposure to sexual possibility situations (Paikoff, 1995).…”
Section: Parenting Stylesmentioning
confidence: 99%
“…A pesar de lo anterior y de lo hallado en esta investigación, autores como Miller (15) afirman encontrar relación directa entre la comunicación (especialmente materna) y la promoción del uso del condón en la primera relación y que esto favorece la utilización del preservativo en las relaciones posteriores asegurando una vida sexual sana (15). Lavielle (9) encontró que la comunicación y la expresión del afecto en la familia como componentes de la funcionalidad familiar influyen de manera positiva en el adolescente al favorecer un nivel adecuado de autoestima y de calidad de vida.…”
Section: Discussionunclassified
“…Timing of these discussions also seems to be relevant to adolescent sexual behavior. For example, Miller, Levin, Whitaker, and Xu (1998) [9] found that mothers' discussion of condom use with adolescents before adolescents' sexual debut was more strongly related to condom use among adolescents than was mothers' discussion of this topic after the onset of sexual activity among adolescents.…”
Section: Parent-adolescent Communication About Sexualitymentioning
confidence: 99%